Psychotherapy: A World of Meanings - Locher, Cosima; Meier, Sibylle; Gaab, Jens (Frontiers in Psychology, 2019)
Despite a wealth of findings that psychotherapy is an effective psychological intervention, the principal mechanisms of psychotherapy change are still in debate. It has been suggested that all forms of psychotherapy provide a context which enables clients to transform the meaning of their experiences and symptoms in such a way as to help clients feel better, and function more adaptively. However, psychotherapy is not the only health care intervention that has been associated with “meaning”: the reason why placebo has effects has also been proposed to be a “meaning response.” Thus, it has been argued that the meaning of treatments has a central impact on beneficial (and by extension, negative) health-related responses. In light of the strong empirical support of a contextual understanding of psychotherapy and its effects, the aim of this conceptual analysis is to examine the role of meaning and its transformation in psychotherapy—in general—and within three different, commonly used psychotherapy modalities.